2006
DOI: 10.1111/j.1365-2257.2006.00819.x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous splenic haematoma in a multiple myeloma patient receiving pegfilgrastim support

Abstract: Growth factors are a significant advance in the supportive care of patients with cancer with a wide range of indications. Frequent side effects of G-CSF include bone pain, headache, fatigue and nausea. We report a case of subcapsular splenic haematoma following pegfilgrastim administration in a 65-year old patient with multiple myeloma. Proposed mechanisms accounting for splenic enlargement include extramedullary haemopoiesis, intrasplenic infiltration by mature and immature myeloid cells and intrasplenic stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Although not significant, probably due to the small sample size, more rapid posttransplantation recoveries of platelets (to >50×10 9 /L) and neutrophils (to more than 1×10 9 /L) were also observed by Bruns et al in chemotherapy-mobilized patients with pegfilgrastim when compared to filgrastim, but only in patients receiving 6 mg, but not 12 mg. 11 In a retrospective study by Steidl et al in newly diagnosed myeloma patients comparing mobilization with cyclophosphamide and either filgrastim or pegfilgrastim (single dose of 12 mg) an earlier recovery postcyclophosphamide of leucocytes to >1×10 9 /L was seen in the pegfilgrastim-treated patients (12 vs. 14 days). 14 While severe toxicities related to pegfilgrastim administration are minimal and limited to bone pain, as with Median in days 17 16 Median in days 17 13 Days from 1 st transplant filgrastim, occasional cases of splenic rupture have been reported after administration of pegfilgrastim, especially in healthy donors; [15][16][17] the incidence of bone pain with pegfilgrastim was not higher in our study than reported with filgrastim. 18,19 A comparable incidence of bone pain with pegfilgrastim and filgrastim was also reported in breast cancer patients.…”
Section: Toxicities Of Pegfilgrastimmentioning
confidence: 47%
“…Although not significant, probably due to the small sample size, more rapid posttransplantation recoveries of platelets (to >50×10 9 /L) and neutrophils (to more than 1×10 9 /L) were also observed by Bruns et al in chemotherapy-mobilized patients with pegfilgrastim when compared to filgrastim, but only in patients receiving 6 mg, but not 12 mg. 11 In a retrospective study by Steidl et al in newly diagnosed myeloma patients comparing mobilization with cyclophosphamide and either filgrastim or pegfilgrastim (single dose of 12 mg) an earlier recovery postcyclophosphamide of leucocytes to >1×10 9 /L was seen in the pegfilgrastim-treated patients (12 vs. 14 days). 14 While severe toxicities related to pegfilgrastim administration are minimal and limited to bone pain, as with Median in days 17 16 Median in days 17 13 Days from 1 st transplant filgrastim, occasional cases of splenic rupture have been reported after administration of pegfilgrastim, especially in healthy donors; [15][16][17] the incidence of bone pain with pegfilgrastim was not higher in our study than reported with filgrastim. 18,19 A comparable incidence of bone pain with pegfilgrastim and filgrastim was also reported in breast cancer patients.…”
Section: Toxicities Of Pegfilgrastimmentioning
confidence: 47%
“…Bone pain and injection site reaction were the commonest reported adverse events, the latter with an incidence similar to previous reports. 24,38 There have been numerous reports of splenic rupture in the literature related to the use of filgrastim [42][43][44] or pegylated filgrastim, [45][46][47] and although routine ultrasound was not performed in study patients, there was no clinical evidence of abdominal pain or anemia, and no increase in bone pain compared to historical controls, during close clinical follow-up of all participants on this study.…”
Section: Discussionmentioning
confidence: 85%
“…23,24 Eleven cases of splenic rupture have been reported in individuals who received G-CSF: four cases in healthy adult donors of PBSC and seven cases in persons with neutropenia or cancer ( Table 1). [26][27][28][29][30][31][32][33][34][35][36] Acute lung injury A few studies have evaluated the effects of G-CSF on pulmonary functions. One study evaluated serial measurements of arterial blood gas in 25 healthy donors who received 10 mg/kg of G-CSF for 5 days.…”
Section: Autoimmune Disordersmentioning
confidence: 99%